COVID-19 DAN DISRUPSI PRAKTIK RITUAL KEAGAMAAN DI INDONESIA: DARI TRADISIONAL KE VIRTUAL (COVID-19 AND THE DISRUPTION OF RELIGIOUS PRACTICES IN INDONESIA: FROM TRADITIONAL TO VIRTUAL) - Abd Hannan (Jurnal Sosiologi Reflektif, 2022)
Social restrictions during the pandemic have caused Islamic authorities in Indonesia to create a number of adaptations of religious rituals. Worship and socio-religious activities that were previously carried out offline (traditionally) have 'moved' to digital platforms. Through a descriptive qualitative research approach with virtual data collection techniques on the internet and social media, this article aims to discuss the phenomenon of disruption of Islamic ritual practices in Indonesia during the pandemic. The results show that this disruption phenomenon has led to a number of debates about the validity and reduction of the sacredness of certain worship practices in Islam. However, on the other hand, the process of disrupting religious ritual facilities has also become a new innovation for Islamic organizations such as NU and Muhammadiyah to organize certain worship practices that require a larger mass and cross regions using digital platforms, for example, the practice of praying together (istighosah), dhikr together (tahlilan), and religious lectures.Pembatasan sosial di masa pandemi menyebabkan otoritas Islam di Indonesia melakukan sejumlah adaptasi ritual keagamaan. Kegiatan ibadah dan sosial-agama yang sebelumnya dilaksanakan secara offline (tradisional) telah ‘berpindah’ ke platform digital. Melalui pendekatan penelitian kualitatif deskriptif dengan teknik pengumpulan data virtual di internet dan sosial media, artikel ini bermaksud untuk membahas fenomena disrupsi religiusitas Islam di Indonesia di masa pandemi. Hasil penelitian menunjukkan bahwa fenomena disrupsi ini telah memunculkan sejumlah perdebatan tentang keabsahan dan reduksi sakralitas praktik ibadah tertentu dalam Islam. Namun demikian, di sisi lain proses disrupsi sarana ritual keagamaan ini juga telah menjadi inovasi baru bagi organisasi Islam seperti NU dan Muhammadiyah untuk penyelenggaraan praktik ibadah tertentu yang memerlukan massa lebih besar dan lintas daerah. Seperti misalnya praktik doa bersama (istighosah), dzikir bersama (tahlilan), dan ceramah-ceramah agama.